UPAYA MENINGKATKAN EFEKTIFITAS BELAJAR LEMPAR CAKRAM DENGAN MEDIA MODIFIKASI CAKRAM DARI PERCA SISWA KELAS IX B SEKOLAH MENENGAH PERTAMA NEGERI 5 PONTIANAK - Muryadi Supriyanto (Universitas Tanjungpura, 2016)
In the process of learning cast disct in SMP Negeri 5 Pontianak is not effective, and as a result the target for curriculum is very low. It causes the narrow yard and it is made from cement that cause the difficulty in learning cast disct in once meeting, students can only get one chance to practice. Based on that things the writer try to improve the effectiveness of learning cast disct of student in SMP Negeri 5Pontianak. The problem in this classroom action research is how to improve the effectiveness of learning cast disct by modifying the disk from scrap of cloth the students of XI B SMP Negeri 5 Pontianak. The researcher use measurement technique/ test and indirect observation technique for collecting the data in this research, and the tool of data collection is skill test to measure the learning of cast disct by holding, swinging, realizing the disk. The acquisition data from the classroom action research are the cycle stages of learning. The result of classroom action research that is done, the researcher can describe in cycle stages. And the write can conclude that the capability of learning the way to hold disc is very effective, the capability of learning the way to swing the disc is very effective, and the capability of learning the last attitude throwing the disc is effective, in the other hand the students’ respond toward the learning is very satisfied. Keyword: the effectiveness of learning cast disct, media, modified the disc from scrap of cloth.